Culture, participation and community development: A case study of Bangladesh. - Orange, Nevin. (University of Ottawa (Canada), 1995)
The objective of this thesis is to critically examine the notion that "participation" and the other catch phrases found within the language of grass roots development, namely "people's participation", "popular participation", "participatory democracy", "bottom-up" and "self-help" development, etc. are a panaces for development. The position that will be taken is that these concepts and ideas are often "western" in origin and are not always in accordance with the existing structures and socio-cultural values and realities of a given non-western society. In effect, this research will examine and analyse how culture can be seen (from a western perspective) to be an impediment or obstacles to the ideals of "participation" and "grass roots" development, and to critically question and reflect upon the concept of participation and grass roots development in Bangladesh.
Keywords: Sociology, Theory and Methods.